2006
DOI: 10.1007/s11908-006-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of rapid HIV antibody tests

Abstract: Rapid HIV antibody tests recently approved by the Food and Drug Administration can help reduce unrecognized infections by improving access to testing in both clinical and nonclinical settings and increase the proportion of those tested who learn their results. Four rapid HIV antibody tests are now available in the United States; two are approved for use at point-of-care sites outside a traditional laboratory. All four tests are interpreted visually. Sites offering rapid HIV testing must periodically run extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 15 publications
(12 reference statements)
1
117
0
1
Order By: Relevance
“…Rapid HIV-1 antibody tests are comparable to ELISAs in both sensitivity (99.3%-100%) and specificity (98.6%-100%). 34 They require no special instrumentation outside of the test kit, and results can be available in as little as 20 to 30 minutes. Some of these kits are licensed for point-of-care testing so that clinics without extensive laboratory facilities (but that meet state and federal standards and have appropriately trained personnel) can perform the tests on-site and report the result to the patient immediately.…”
Section: Detection Of Hiv-1 Antibodiesmentioning
confidence: 99%
“…Rapid HIV-1 antibody tests are comparable to ELISAs in both sensitivity (99.3%-100%) and specificity (98.6%-100%). 34 They require no special instrumentation outside of the test kit, and results can be available in as little as 20 to 30 minutes. Some of these kits are licensed for point-of-care testing so that clinics without extensive laboratory facilities (but that meet state and federal standards and have appropriately trained personnel) can perform the tests on-site and report the result to the patient immediately.…”
Section: Detection Of Hiv-1 Antibodiesmentioning
confidence: 99%
“…Although, the majority of these rapid tests utilize whole blood, plasma and finger stick blood specimens, a few tests employ nonconventional specimens, such as saliva, oral mucosal fluid and urine [4,5]. Oral fluid-based rapid tests have potential advantages over blood-based rapid tests because of their convenience, noninvasiveness, ease of specimen collection, cultural acceptance, high accuracy and rapidity [4,[6][7][8].…”
Section: Rapid Point-of-care Hiv Tests and Use Of Nonconventional Specimentioning
confidence: 99%
“…2 In recent years, lack of identification of maternal HIV-infection status has been the primary reason for new infant HIV infections; effective interventions cannot be implemented unless maternal HIV status is known. Rapid HIV antibody testing methods now allow identification of HIV-infected women or HIV-exposed infants in 20 to 60 minutes [3][4][5] (see also www.cdc.gov/ hiv/topics/testing/rapid/index.htm). Studies have demonstrated the effectiveness of ARV prophylaxis for preventing MTCT of HIV, even when prophylaxis is initiated after the birth of the infant.…”
Section: Why Is a New Statement Needed Now?mentioning
confidence: 99%
“…3,5,14 These are screening tests, which means that a positive test result requires confirmation with an IFA or Western blot assay. The rapid antibody test is more sensitive and more specific than the conventional EIA, so a conventional EIA is not used as the confirmatory test for a rapid HIV antibody test.…”
Section: Hiv Testingmentioning
confidence: 99%